Adult T-cells impair neonatal cardiac regeneration. (25th November 2020) - Dolejsi, T; Schuetz, T; Delgobo, M; Tortola, L; Bauer, A; Ruschitzka, F; Penninger, J.M; Ramos, G; Haubner, B.J
Abstract: Background: Cardiac remodeling and subsequent heart failure remain critical issues after myocardial infarction (MI). Complete cardiac regeneration was shown recently in a neonatal mouse model of MI. This cardiac regenerative potential is limited to the first few postnatal days and its decline parallels with the maturation of the adaptive immune system. Purpose: Herein, we hypothesized that the T-cell maturation status critically impacts the myocardial healing outcomes in neonates and contributes to the shift from regenerative to scarring phenotype observed shortly after birth. Methods: The post-MI immune responses were characterized in postnatal day one (P1, regenerative) compared to seven-day old (P7, scarring) mice subjected to permanent left anterior descending artery (LAD) ligation. The myocardial leukocyte infiltrate was phenotyped by flow cytometry at 36 hours and five days after LAD ligation. Next, we studied neonatal post-MI repair in lymphocyte-deficient Rag2 knock-out (KO) mice subjected to LAD ligation. Moreover, we adoptively transferred syngeneic splenic Thy 1.1+ T-cells obtained from adult donors into P1 versus P7 recipients and then assessed their impact on post-MI healing. Results: LAD ligation induced a robust early inflammatory response (36h post-MI) in both age groups. The in situ inflammation was, nevertheless, rapidly resolved in P1-, but not in P7-infarcted animals. The distinct age groups showed a similar profile of cardiac myeloid cell infiltration but showed remarkable differences in the lymphoid compartment. P1-infarcted mice showed an early recruitment of γδT-cells, whereas P7-infarcted mice exhibited a prominent infiltration of αβT-cells. Of note, neonatal cardiac regeneration was not altered in neonatal lymphocyte-deficient (Rag2 KO) animals. However, the adoptive transfer of adult T-cells had several consequences in neonatal and one week old mice subjected to ischemic injury. P1-infarcted mice transferred with adult T-cells showed an adult-like healing phenotype, marked by an irreversible cardiac functional impairment (assessed by echocardiography) and increased fibrosis. This is in sharp contrast to the regenerative phenotype typically observed in untreated age-matched controls. Furthermore, P7-infarcted mice transferred with adult T-cell showed significantly decreased survival rate after LAD ligation. Conclusion: Neonatal hearts demonstrate rapid clearance of the ischemia-induced leukocyte infiltration, further reflecting the known fact of fast cardiac regeneration in newborn rodents. Of note, the adoptive transfer of adult T-cells into neonate recipients partially blocked cardiac regeneration and promoted an irreversible functional impairment. These data indicate that the cardiac repair process, and its related "regeneration vs. scarring" dichotomy, is critically impacted by the T-cell development status. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Innsbruck Medical University, Medizinischer Forschungsfonds Tirol